2015
DOI: 10.1177/1938640015569766
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma With Chronic Osteomyelitis

Abstract: Therapeutic, Level IV: Case report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…This option was not applicable in our case due to the size and depth of the cSCC in our patient where it invaded an important part of the calcaneus. Another risk factor was highlighted by Wukich DK et al who reported a case of cSCC in a patient with longstanding chronic osteomyelitis [ 10 ]. Their patient has failed multiple reconstructive plastic and orthopedic procedures so he was treated by below-knee amputation.…”
Section: Discussionmentioning
confidence: 99%
“…This option was not applicable in our case due to the size and depth of the cSCC in our patient where it invaded an important part of the calcaneus. Another risk factor was highlighted by Wukich DK et al who reported a case of cSCC in a patient with longstanding chronic osteomyelitis [ 10 ]. Their patient has failed multiple reconstructive plastic and orthopedic procedures so he was treated by below-knee amputation.…”
Section: Discussionmentioning
confidence: 99%
“…1 Because squamous cell carcinoma of the lower extremity has a high likelihood for metastases (up to 30%), early diagnosis is critical. 27 The five-year recurrence rate of primary lesion is 8% with a good prognosis, while the five-year rate of metastasis is 5% 5,8 with a poorer prognosis, in particular with regional lymph node involvement, which occurs in 85% of cases. 25,8 Plain film radiography of any limb squamous cell carcinoma is crucial to assess for bone involvement.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Other aetiologies include ionising radiation, human papilloma virus infection, chemical agents, immunocompromised patients, genetic conditions, traumatised skin and non-healing skin also known as Marjolin’s ulcer. 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ces signes doivent inciter à la réalisation des prélèvements biopsiques et à l’étude histopathologique [ 6 ]. Un bilan d’extension complet clinique et radiologique doit être pratiqué en préopératoire et se base idéalement sur la tomographie avec émission de positrons (PET Scan) [ 7 ], il est dans la majorité des cas négatif, comme c’est le cas de notre observation. Le stade d’extension de la tumeur représente le principal facteur pronostic [ 1 ] et oriente l’attitude thérapeutique.…”
Section: Discussionunclassified